2010
DOI: 10.1016/j.physbeh.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain somatostatin 2 receptors stimulates feeding in mice: Analysis of food intake microstructure

Abstract: We recently reported that the oligosomatostatin receptor agonist, ODT8-SST increases food intake in rats via the somatostatin2 receptor (sst2). We characterized ingestive behavior following intracerebroventricular (icv) injection of a selective sst2 agonist in freely fed mice during the light phase. The sst2 agonist (0.01, 0.03, 0.1, 0.3 or 1µg/mouse) injected icv under short inhalation anesthesia dose-dependently increased cumulative light phase food intake over 4h compared to vehicle with a 3.1-times increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 44 publications
3
72
0
1
Order By: Relevance
“…There may be differences in the effects of octreotide and somatostatin. Octreotide may have a direct action on the brain (36). However, Goldstone et al (7) found no direct effect of octreotide on food reward behaviors in NW subjects or, when given with insulin, on postprandial hunger or fullness after RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…There may be differences in the effects of octreotide and somatostatin. Octreotide may have a direct action on the brain (36). However, Goldstone et al (7) found no direct effect of octreotide on food reward behaviors in NW subjects or, when given with insulin, on postprandial hunger or fullness after RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established the automated system in mice and shown the same food intake, as observed manually during the light and dark phase (52). Because these data were generated in a different species, we performed an additional experiment in rats to validate automated vs. manual measurement of dark-phase food intake.…”
Section: Methodsmentioning
confidence: 99%
“…Food intake pattern was assessed as established in our previous studies (21,52) using an automated episodic food intake-monitoring system for regular pellet rat food (BioDAQ, Research Diets, New Brunswick, NJ). Water was provided ad libitum from regular water bottles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructure analysis of food intake was performed using the BioDAQ episodic food intake monitor for mice (Research Diets, New Brunswick, NJ). This system allows the continuous monitoring of meal patterns in undisturbed mice with minimal human interference as described in previously published studies (49). The system weighs the food hopper (Ϯ0.01 g) second by second and detects not eating as weight stable, and eating as weight unstable.…”
Section: Methodsmentioning
confidence: 99%